1998
DOI: 10.1111/j.1748-5827.1998.tb03596.x
|View full text |Cite
|
Sign up to set email alerts
|

Urethral sphincter mechanism incompetence in the male dog: importance of bladder neck position, proximal urethral length and castration

Abstract: The radiographs of 37 incontinent adult male dogs with urethral sphincter mechanism incompetence were compared with those of 28 control dogs to determine if, as in the bitch, differences in bladder neck position and urethral length were implicated in the pathophysiology of urethral sphincter mechanism incompetence. Bladder neck position was significantly different; compared with continent dogs, incontinent animals were significantly more likely (P < 0.005) to have intrapelvic than intra-abdominal bladder necks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 8 publications
1
34
0
Order By: Relevance
“…Shortening of the urethra displaces the bladder caudally into the pelvic canal, potentially preventing exposure of the bladder neck to the intraabdominal pressure. 30 In our dogs, postoperative positive-contrast studies demonstrated that the bladders were not displaced in the pelvis (Fig 7); however, the extent of the tumor into the proximal urethra should be taken into account before using this surgical technique. In our dogs, resection of o2 cm of urethra was sufficient to provide clean resection margins.…”
Section: Discussionmentioning
confidence: 63%
“…Shortening of the urethra displaces the bladder caudally into the pelvic canal, potentially preventing exposure of the bladder neck to the intraabdominal pressure. 30 In our dogs, postoperative positive-contrast studies demonstrated that the bladders were not displaced in the pelvis (Fig 7); however, the extent of the tumor into the proximal urethra should be taken into account before using this surgical technique. In our dogs, resection of o2 cm of urethra was sufficient to provide clean resection margins.…”
Section: Discussionmentioning
confidence: 63%
“…Measurement of free or bioavailable testosterone could be useful when the TT concentration is not definitively diagnostic. In dogs, one of the side‐effects of neutering is the development of urinary incontinence . Interestingly, GnRH analogue treatment to lower plasma LH and FSH concentrations results in a temporary return of continence or an improvement of symptoms during the treatment periods .…”
Section: Discussionmentioning
confidence: 99%
“…Information regarding previous medical therapy was not recorded for 2 dogs. Seven dogs had one or more previous surgical or endoscopic procedures for incontinence, including submucosal collagen injections (4 dogs), neoureterocystostomy (4), and laser ablation of intramural ectopic ureters (2).…”
Section: Study Populationmentioning
confidence: 99%
“…Final continence scores were obtained in 25 of 27 dogs (Fig 3), with a median follow-up of 12.5 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) months. Median (IQR) continence scores were significantly improved (P < .0001) between the preoperative period (2 [1][2][3][4]) and last follow-up period (9 [8-10]). Overall owner satisfaction was high, with 22 owners describing themselves as very satisfied, 2 as satisfied, and 3 as unsatisfied.…”
Section: Continence Scoresmentioning
confidence: 99%
See 1 more Smart Citation